Company Size and the Presence of Independent Commissioners, Can They Affect the Disclosure of Enterprise Risk Management? - Christian, Ferry; Rasyid, Syarifuddin; Ferdiansah, Muhammad Irdam (Program Studi Akuntansi FPEB UPI, 2024)
This study aims to determine the effect of company size and independent commissioners on the disclosure of Enterprise Risk Management. The object of this study are manufacturing companies listed on the Indonesia Stock Exchange during 2019-2021 with a total of 31 companies that meet the criteria using a purposive sampling technique. Data analysis using SPSS. The results of the study show that company size has a significant effect on Enterprise Risk Management disclosure. Meanwhile, the Independent Commissioner has no effect on the disclosure of Enterprise Risk Management. These results contribute to investors for investment decisions based on company size. This means that the larger the size of the company, the company tends to disclose more extensive information about risk management.